Emergent decoloniality in Indonesian English Coursebooks - Af'idatul Husniyah; Hasti Rahmaningtyas; Titien Indrianti (Research and Innovation in Language Learning, 2025)
This study investigates the decolonial aspects of English textbooks developed by the Indonesian government for high school students under the Kurikulum Merdeka, focusing on their cultural and pedagogical narratives. It employs the decoloniality framework proposed by Núñéz-Pardo and integrates Fairclough's three-dimensional model of Critical Discourse Analysis to reveal the power dynamics and ideologies embedded in the textbooks. The analysis of four textbooks identifies numerous signs of emergent decoloniality. These include culturally embedded representations of Indonesian society, such as the use of local names, depictions of traditional fruits, and diverse clothing styles, including students wearing veils and those not wearing veils. The textbooks also highlight Indonesia's societal diversity through portrayals of varied skin tones. Although decolonization is not yet a widely recognized concept in ELT in Indonesia, the government has made significant attempts toward embracing and promoting Indonesian local cultural roots. Through the lens of Fairclough's and Núñéz-Pardo's framework, these textbooks can be interpreted as a challenge to hegemonic Western-centric narratives. In this case, English is seen as a medium for intercultural communication rather than a tool for cultural dominance. By shifting away from centring English within a Western framework, these coursebooks represent a promising step toward decoloniality in English teaching.